The Urgency of War Crimes Regulation in Indonesian Criminal Law - Desia Rakhma Banjarani; Febrian Febrian; Mada Apriandi Zuhir; Neisa Angrum Adisti (Fiat Justisia: Jurnal Ilmu Hukum, 2023)
Indonesia has Law Number 26 of 2000 concerning the Human Rights Court or the Law on Human Rights Courts, similar to the Rome Statute. However, this law does not regulate war crimes, while the Rome Statute specifically regulates war crimes. Meanwhile, the perpetrators of war crimes must be tried at any time because those crimes do not know the expiration date. Meanwhile, the perpetrators of war crimes must be tried at any time because those crimes do not know the expiration date. It is the background of this research that the problem will be discussed: How are war crimes provisions in humanitarian law and international criminal law? Why do war crimes need to be regulated in Indonesian criminal law? This type of research is normative juridical research with a statute approach through qualitative descriptive analysis. The results of this study show that the regulation of war crimes is governed by humanitarian law and international criminal law. In humanitarian law, war crimes are regulated in the 1907 Hague Convention, the 1949 Geneva Convention, The Declaration on the Protection of Women and Children in Emergency 1974, and Additional Protocol II Geneva Convention 1977. Meanwhile, international criminal law regulates the responsibility of war crime perpetrators in the IMT Charter 1945, IMTFE Charter 1946, the 1993 ICTY Statute, the 1994 ICTR Statute, and the 1998 Rome Statute. The urgency of regulating war crimes in Indonesian law is due to four aspects: 1) Indonesia has ratified the 1949 Geneva Convention. 2) No regulations in Indonesia regulate war crimes, even in the 2023 Criminal Code. 3) Indonesia is part of the international community. 4) Law enforcement armed conflict cases in Indonesia is unresolved.